2018
DOI: 10.4317/jced.54858
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of surface sealants effect on the surface roughness of Nano-hybrid composite after polishing with One-Step system (in-vitro)

Abstract: BackgroundThe clinical use of composite resins has increased substantially due to increased esthetic demands by patients, improvements in formulation, and simplification of bonding procedures. Use of surface sealants is recommended to improve surface smoothness of composite restorations. The aim of this study was to evaluate the effect of surface sealants on the surface roughness of nano-hybrid composite after polishing with One-Step system.Material and MethodsUsing a silicon mold, 56 specimens of 10 mm diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…However, there still needs to be a consensus regarding the effects of surface sealant on composite resin restorations. While some studies reported a lower Ra value when composite resin restorations have surface sealant used as the last step [24][25][26], other studies have reported no significant difference [23,[27][28][29].…”
Section: Introductionmentioning
confidence: 96%
“…However, there still needs to be a consensus regarding the effects of surface sealant on composite resin restorations. While some studies reported a lower Ra value when composite resin restorations have surface sealant used as the last step [24][25][26], other studies have reported no significant difference [23,[27][28][29].…”
Section: Introductionmentioning
confidence: 96%